Sports metaverses: theory and practice - Skarzhinskaya, E. N.; Ermakov, A. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the current state of the problem of developing a sports metaverse in the digital space based on a theoretical analysis of information sources, as well as cases of holding sporting events in metaverses.